2022
DOI: 10.1177/00420859211068465
|View full text |Cite
|
Sign up to set email alerts
|

Back in on the Outside: Racialized Exclusion at Chicago's School/Prison Nexus and the Promise of Student Voice

Abstract: Most students released from detention never return to school. This study uses youth participatory action research and Social Justice Youth Development Theory to explore the experiences of those who do. Findings demonstrate that formerly incarcerated students want to return to school but face institutionalized resistance that amounts to racialized exclusion, violence, and state-sanctioned neglect at Chicago's school/prison nexus. We offer recommendations on how to “reverse” the school-to-prison pipeline by shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Put differently, our findings add to the literature on the intertwined web of experiences and outcomes that characterize the STPP. Our findings are also consistent with scholarship that has shown how schools and other institutions, such as the criminal legal system, are interrelated (Gardner et al, 2022;Kautz, 2023;Shedd, 2015), suggesting that while schools are critical to focus on, education researchers also should consider how these other institutions shape school life and academic outcomes. In other words, we hope education researchers continue to examine the extent to which experiences with individuals, processes, or systems not directly related to teaching and learning can shape students' academic outcomes.…”
Section: Final Implicationssupporting
confidence: 89%
“…Put differently, our findings add to the literature on the intertwined web of experiences and outcomes that characterize the STPP. Our findings are also consistent with scholarship that has shown how schools and other institutions, such as the criminal legal system, are interrelated (Gardner et al, 2022;Kautz, 2023;Shedd, 2015), suggesting that while schools are critical to focus on, education researchers also should consider how these other institutions shape school life and academic outcomes. In other words, we hope education researchers continue to examine the extent to which experiences with individuals, processes, or systems not directly related to teaching and learning can shape students' academic outcomes.…”
Section: Final Implicationssupporting
confidence: 89%
“…Namely, Sinclair et al (2021) conducted qualitative semi-structured interviews with transition specialists ( n = 7) and young offenders ( n = 8) who participated in a 4 years reentry project in the Pacific Northwest, examining what services best support youths' reentry into a school setting. Gardner et al (2022) interviewed 90 students attempting to return to school after incarceration and 17 adults (parents, probation officers, school administrators, formerly incarcerated citizens) in Chicago, assessing their experiences with returning to school. Despite these recent developments to incorporate the voice of youth and their experiences with school reentry, recent studies still exhibit methodological limitations.…”
Section: Prior Literaturementioning
confidence: 99%
“…Research on community reintegration and school reentry has identified numerous difficulties and barriers that can prevent youth from successfully transitioning back to school after their release from a juvenile justice facility. Some barriers include lack of family, school, and social supports, lack of academic skills and being far behind in school, negative peer associations, substance use, a lack of consistency across varying school systems (e.g., credits earned, calendars), and even direct school resistance, exclusion, and stigma (Baltodano et al, 2005; Feierman et al, 2010; Gardner et al, 2022; Garwood, 2015; Kubek et al, 2020; Marshall et al, 2012; Mathur & Clark, 2014; Miller et al, 2019; O’Neill et al, 2017; Siennick & Staff, 2008; Sinclair et al, 2021; Unruh, 2005; Unruh & Bullis, 2005; Wallace, 2012). Students may also lack the appropriate required records and documents needed for reenrollment (e.g., birth certificate, residency verification, immunization records), which in some instances are not forwarded to the student’s community school from the juvenile justice system (Feierman et al, 2010; Marshall et al, 2012; O’Neill et al, 2017; Wallace, 2012).…”
Section: Prior Literaturementioning
confidence: 99%